PID Control Tuning Using PSO For Prosthetic Hand System - Rozaimi, Ghazali (Research India Publications, 2016)
Hand is one of the part human bodies with highest complex structures to control the movement involving a lot of numbers nerve endings connected.Amputees are disable person who has difficulties when dealing with their routine life activities because of physical problem such as lost all or part of an arm,hand or leg.The hand,the nerve endings are required high capabilities to control the velocity, positioning,force and movement of fingers.The main problems related to the prosthetic device are its functionality,lack of intuitive control and insufficient feedback due to lack of robust capability during ongoing operation.The primary purpose for this project is to focus on designing the prosthetic hand consist of controller based on Proportional Integral Derivative (PID) and Particle Swarm Optimization (PSO) control algorithms for patients with wrist and arm amputees.PSO is an optimization technique,inspired by social behavior of bird flocking or fish schooling.It can be used to tune the PID control parameters in order to achieve the desired performance target.Thus,the control technique for prosthetic hand positioning control by using PID controller that is tuned by PSO will be described thoroughly in this paper.The result is proved through simulation and in experiment,thus verifying the research hypothesis.